Strong enhancement of electrical conductivity in two-dimensional micrometer-sized RuO2 nanosheets for flexible transparent electrodes. Issue 21 (17th May 2017) - Yoo, Somi; Kim, Jeongmin; Moon, Hongjae; Kim, Se Yun; Ko, Dong-su; Shin, Weon Ho; Hwang, Sungwoo; Jung, Doh Won; Sul, Soohwan; Kwak, Chan; Roh, Jong Wook; Lee, Wooyoung
Abstract : Ag NPs on the surface of RuO2 NSs increased the electrical conductivity by up to 3700%. Abstract : The enhancement in electrical transport properties of exfoliated individual RuO2 NSs was systemically investigated for their application in flexible electronics and optoelectronics. Decoration of Ag NPs on the surface of the RuO2 NSs provides donor electrons and dramatically increases the electrical conductivity of the monolayer RuO2 NSs by up to 3700%. The n-type doping behavior was confirmed via Hall measurement analysis of the doped RuO2 NSs. The layer number- and temperature-dependence of the conductivity were also investigated. Moreover, carrier concentration and mobility were obtained from Hall measurements, indicating that the undoped RuO2 NSs had ambipolar transport and semi-metallic characteristics. Moreover, the Ag-doped RuO2 NS multilayer films on polycarbonate substrates were demonstrated by the Langmuir–Blodgett assembly methods, showing one-third reduction in the sheet resistance and extraordinarily high bending stability that the change in the resistance was less than 1% over 50 000 cycles.